KECURANGAN AKADEMIK (ACADEMIC DISHONETY) PADA MAHASISWA FAKULAS TARBIYAH DAN KEGURUAN (FTK) UIN AR-RANIRY - Darmiah Darmiah; Tria Marvida (PIONIR: JURNAL PENDIDIKAN, 2023)
The amount of academic cheating committed by students creates a bad image among students. One of the causes is due to the demands of value. This value is an assessment of learning outcomes which is used as a measure of the success of a quality education. Ideally, students as an example of the next generation of the nation should make this country progress with their works. But in reality the demands and high standards of grades make students do everything they can including academic cheating. This certainly makes the academic community smeared because of the cheating. This research is a type of quantitative research. The research design used is exploratory descriptive. The population in this study is students UIN Ar-Raniry class of 2019 who are taking micro teaching courses with a total of 12 students. Data collection was carried out using questionnaires shared with the help of google forms. Data analysis is descriptive statistical analysis. The form of academic fraud committed by students of the UIN Ar-Raniry Banda Aceh is plagiarism and cheating.